Peningkatan pemahaman dan kualitas Lesson Plan guru melalui Inquiry Collaborative Learning (ICL) - Prayitno, Baskoro Adi; Sri Widoretno; Bowo Sugiharto; Chandra Adi Prabowo; Dwi Oetomo; Faturrahim, Muhammad Ilham; Aprilia, Nur Isna; Chasanah, Elisa Hidayatul; Ismara, Viana; Kartika, Rahma Eka (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
Inquiry Collaborative Learning (ICL) is a learning model based on the scientific method, enhanced by collaborative elements. This model aims to encourage students not only to memorize scientific concepts but also to understand scientific processes and the attitudes of scientists. This activity aimed to evaluate the impact of training, modeling, and mentoring in implementing ICL on teachers' understanding and the quality of ICL-based lesson plans in Ngawi Regency. The program involved 80 participants, comprising 70 teachers from the IPA MGMP and 10 members of the implementing team, representing 13 public and 47 private Islamic junior high schools. The activities were conducted using a blended learning approach, including theoretical training, modeling, online mentoring for lesson plan development, and classroom implementation of ICL. The results showed a significant improvement in teachers' understanding, from 60% before the program to 85% afterward. The quality of lesson plans also improved in terms of setting learning objectives, analyzing the structure and flow of materials, designing active learning-based teaching scenarios, and evaluating the learning process. These findings affirm that ICL-based training, modeling, and mentoring effectively enhance teachers' understanding and skills in implementing scientific process-based teaching